Advances in Biology and Therapy of Multiple Myeloma Volume 2: Translational and Clinical Research - Munshi, Nikhil C.; Munshi, Nikhil C.; Anderson, Kenneth C.; Anderson, Kenneth C. (Springer New York : Imprint: Springer, 2013)
Despite the advances in conventional, and novel agent and high dose chemotherapy, multiple myeloma remains incurable. In order to overcome resistance to current therapies and improve patient outcome, novel biologically-based treatment approaches are being developed. Current translational research in multiple myeloma focusing on the development of molecularly-based novel targeted single-agent and combination therapies has great promise to achieve high frequency and durable responses in the majority of patients.   This volume will focus on biology of multiple myeloma, especially on oncogenomic changes, cell signaling pathways and intermediate molecules that are being investigated for development of novel therapies. The book will present newer developments, providing an emphasis on basic science, as well as its significant clinical impact.